Voluntary pulmonary function screening with GOLD standard: an effective and simple approach to detect lung obstruction - Wang, Shengyu; Gong, Wei; Tian, Yao; Yang, Min (Journal of Thoracic Disease, 2015)
Background: The prevalence of lung obstruction is probably underestimated. Early detection and screening may alter the course and prognosis associated with lung disease. We investigated the effectiveness of voluntary lung function screening program and the agreement between the Global Initiative for Chronic Obstructive Lung Disease (GOLD) and the lower limit of normal (LLN) standard for public screening in Xi’an China. Methods: Pulmonary function testing was conducted on volunteers recruited from eight community centers in Xi’an, China between July and August 2012. Participants underwent three forced vital capacity (FVC) maneuvers. The maneuver with the best FEV1 was retained. Participants filled out a medical history survey before undergoing pulmonary function testing. Patients that self-reported lung disease on the health survey were excluded from the analysis. Results: A total of 803 volunteers participated in this study. And 722 participants (93.8%) did not self-report chronic lung disease and were analyzed. Of these participants, 143 subjects (19.8%) were diagnosed by GOLD standard and 134 subjects (18.6%) had obstruction with LLN definition. GOLD definition can identify more asymptomatic subjects (19.1%) with respect to LLN. GOLD definition can detect more lung obstruction in elder subjects compared with young people, the difference is significant (P=0.0007). The overall agreement between the 2 methods was good: the kappa estimate was 0.822. The agreement in subjects aged 40-49, 50-59 and 60-69 years was good: the kappa estimate was 0.82, 0.936 and 0.907 respectively and the agreement in subjects aged 18-29 was inferior: the kappa estimate was only 0.555. Conclusions: Voluntary lung function screening program with GOLD standard may be a simple and effective approach to ensuring high yield detection of lung obstruction in subjects aged 40-69.